Do Firms Withhold Loan Covenant Details? - Li, Edward Xuejun; Neamtiu, Monica; Tu, Zhiyuan (The Accounting Review, 2024)
ABSTRACT We study firms’ decisions to withhold loan covenant details by focusing on a unique disclosure-related cost. Prior research documents the prevalence of tight initial covenants that are selectively relaxed in future renegotiations. This uncertainty in renegotiation outcomes can generate a disclosure-related cost because disclosing a snapshot of initial covenants with a high likelihood of violation could lead to harmful outsider reactions (e.g., trade credit cuts) to violations that may be eventually cured. We hypothesize and find that, when firms are likely to face tighter initial covenants and more renegotiations, they are more likely to withhold covenant details, particularly when under pressure from trade creditors. Our inference is robust to controlling for firms’ obligation to disclose (i.e., contract materiality) and future performance. Prior research has found that the precise covenant details of many loans are not publicly available. We are the first to offer a systematic explanation related to disclosure costs. JEL Classifications: M41; D82; G21; L14.